Epidemiological Study of Malaria Cases 2018-2021 in Bintan District, Riau Archipelago Province, Indonesia - Dian Nugraha; Bagoes Widjanarko; Budiyono Budiyono; Rinaldi Daswito (Humanistic Network for Science and Technology (HNST), 2023)
Malaria in Bintan Regency is a health problem because several areas are endemic. This study aimed to describe the epidemiology of malaria cases in Bintan Regency in 2018-2021 based on person, place, and time. This type of research was descriptive with a population of all malaria cases recorded at the Bintan District Health Office for the period January 2018 to December 2021. The sample was the total population. Variables collected include trend of malaria cases, annual API, age, sex, plasmodium type, type of case, time, and place. Secondary data was obtained from the SISMAL application of the Riau Islands Province Health Office. Data analysis was performed to describe malaria endemicity. The results of the study showed that the endemicity of malaria in Bintan Regency from 2018-2021 was getting better. The majority of malaria cases for the 2018-2021 period were 15-64 years old and male. Based on the highest time in May and July 2020 with distribution locations in the working areas of Kawal health center and Berakit health center. The type of plasmodium falciparum parasite in 2018-2019 and 2020-2021 was infected with plasmodium vivax. The case type was derived from the original malaria case. The majority of treatments used Artemisinin-Based Combination Therapy (ACT).Keywords: malaria; plasmodium; archipelago